Capability Development in an Offshoring Context: How, Why and by Whom - Manya Jaura Lind (Copenhagen Business School (CBS), 2016)
Capability development can be defined as deliberate firm-level investment involving a search and learning process aimed at modifying or enhancing existing capabilities. Increasingly, firms are relocating advanced services to offshore locations resulting in the challenge of capability development in the offshore unit. Guided by the research question – what drives or impedes capability development in an offshoring context – the purpose of this thesis is to investigate how an idiosyncratic offshoring context affects capability development. The thesis consists of three papers using various datasets and qualitative methods that investigate capability development in an offshoring context. The first paper investigates how capability development takes place for a service-provider firm at the activity level. The second paper examines the transition made by a captive offshore unit, from performing standardized activities to R&D activities. The third paper examines capability development at the cluster level, and examines how spillovers from firms contribute to the emergence and evolution of clusters. Overall, this thesis argues that capability development is a path dependent process, and the offshoring context complicates the identification of capabilities lacking, the resources required to develop these capabilities and the alignment of supporting organizational processes. Captive offshore units and local service providers often perform back-office or standardized tasks that have been disaggregated from the value chain. In these cases, capability development presents a challenge, as firms need to take deliberate actions in order to develop capabilities, and identify the external linkages they must form to aid the capability development process.
hdl:10398/9368
Keywords: 650